PENGARUH KONSENTRASI DAN PANGSA PASAR TERHADAP PENGAMBILAN RESIKO BANK - Sesario Tri Nur Hendra; Deny Dwi Hartomo (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2017)
This study aimed to examine the effect of concentration (Herfindahl index, concentration ratio) and market share (Market Share) torisk taking (Zscore) on go public banks in Indonesia. This study using purposive sampling method with a sample size of 40 biggest bank by assets in the country of Indonesia in 2010-2014.These results indicate that concentration with Herfindahl index proxies positive and significant effect on risk-taking. While the concentration of the proxy Concentration ratio and market share but not significant positive effect on risk-taking.